Impact of Electric Stimulation on Residual Hearing. - Dillon, Margaret T.; Bucker, Andrea L.; Adunka, Marcia C.; King, English R.; Adunka, Oliver F.; Buchman, Craig A.; Pillsbury, Harold C. (Journal of the American Academy of Audiology, 2015)
Background: Candidacy criteria for cochlear implantation are expanding to include patients with substantial low-to-mid frequency hearing sensitivity. Postoperative hearing preservation has been achieved in cochlear implant recipients, though with variable outcomes. Previous investigations on postoperative hearing preservation outcomes have evaluated intraoperative procedures. There has been limited review as to whether electric stimulation influences hearing preservation. Purpose: The purpose of this analysis was to evaluate whether charge levels associated with electric stimulation influence postoperative hearing preservation within the first year of listening experience. Research Design: Retrospective analysis of unaided residual hearing and charge levels. Study Sample: Twenty-eight cochlear implant recipients with postoperative residual hearing in the operative ear and at least 12 mo of listening experience with electric-acoustic stimulation (EAS). Data Collection and Analysis: Assessment intervals included initial cochlear implant activation, initial EAS activation, and 3-, 6-, and 12-mo postinitial EAS activation. A masked low-frequency bone-conduction (BC) pure-tone average (PTA) was calculated for all participants at each assessment interval. Charge levels for each electrode were determined using the most comfortable loudness level and pulse width values. Charge levels associated with different regions of the electrode array were compared to the change in the low-frequency BC PTA between two consecutive intervals. Results: Charge levels had little to no association with the postoperative change in low-frequency BC PTA within the first year of listening experience. Conclusions: Electric charge levels do not appear to be reliably related to the subsequent loss of residual low-frequency hearing in the implanted ear within the first year of EAS listening experience.